2008
DOI: 10.1111/j.1471-4159.2008.05453.x
|View full text |Cite
|
Sign up to set email alerts
|

Functions of human bitter taste receptors depend on N‐glycosylation

Abstract: Human bitter taste receptors of the TAS2R gene family play a crucial role as warning sensors against the ingestion of toxic food compounds. Moreover, the genetically highly polymorphic hTAS2Rs recognize an enormous number of structurally diverse toxic and non-toxic bitter substances, and hence, may substantially influence our individual eating habits. Heterologous expression in mammalian cells is a useful tool to investigate interactions between these receptors and their agonists. However, many bitter taste re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 46 publications
3
48
0
3
Order By: Relevance
“…S4A) with similar sites predicted in both Q8NHA5 and GABA B-1B (supplementary material Fig. S4B,C), where they have been associated with bitter taste receptor function in previous studies (Bufe et al, 2002;Reichling et al, 2008). Because our data support a role for the overactivation of Q8NHA5 in response to phenylthiourea, we conclude that this receptor could be activated by phenylthiourea, with the potential of regulating neuropsychiatric function.…”
Section: Discussionsupporting
confidence: 81%
“…S4A) with similar sites predicted in both Q8NHA5 and GABA B-1B (supplementary material Fig. S4B,C), where they have been associated with bitter taste receptor function in previous studies (Bufe et al, 2002;Reichling et al, 2008). Because our data support a role for the overactivation of Q8NHA5 in response to phenylthiourea, we conclude that this receptor could be activated by phenylthiourea, with the potential of regulating neuropsychiatric function.…”
Section: Discussionsupporting
confidence: 81%
“…The ATrM1 clone was not functional probably because of missing 4 Asn-linked putative glycosylation sites. It has been shown that glycosylation is critical for GPCR function [8, 34, 44, 45]. In marked contrast, HEK293/Gα16gust44 cells expressing ATrM2 or ATrM3 receptors were both robustly activated by AT in a dose-responsive manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the T2Rs share a conserved consensus site for asparagine-linked glycosylation within the second extracellular loop. This site is known to be important for membrane targeting and receptor function (Reichling et al, 2008). T2Rs enable humans to perceive thousands of bitter compounds, since most receptors are able to recognize several different types of ligands or even whole chemical families.…”
Section: Accepted Manuscriptmentioning
confidence: 99%